ICS-formoterol reliever therapy stepwise treatment algorithm for adult asthma. Issue 1 (9th January 2020) - Beasley, Richard; Braithwaite, Irene; Semprini, Alex; Kearns, Ciléin; Weatherall, Mark; Harrison, Tim W.; Papi, Alberto; Pavord, Ian D.
A stepwise approach to the pharmacological treatment of asthma is a key feature of current asthma guidelines [1–4]. Through algorithms, treatment intensity is "stepped up" to obtain asthma control and reduce the risk of exacerbations, and "stepped down" after a period of prolonged control and absence of exacerbations. Traditional algorithms advocated short-acting β2 -agonist (SABA) reliever therapy for all levels of severity, initially as sole therapy at Step 1, together with maintenance "low dose" inhaled corticosteroids (ICS) at Step 2, with maintenance ICS/long-acting β2 -agonist (LABA) at "low", "moderate" or "high" doses at Steps 3 and 4, and finally with "add-on" therapies at Step 5. A practical "anti-inflammatory reliever therapy"-based algorithm based on the GINA 2019 update is presented, together with a prototype action plan to facilitate its implementation. http://bit.ly/33C2s5u